Identification of cerebrospinal fluid biomarker candidates for anti-N-methyl-D-aspartate receptor encephalitis: High-throughput proteomic investigation - Li, Yuchen; Yang, Keyu; Zhang, Fang; Wang, Jing; Shen, Huijun; Liu, Miaomiao; Guo, Junhong; Wang, Jie (Frontiers in Immunology, 2022)
Background Although the diagnosis is mainly dependent on the detection of anti-N-methyl-D-aspartate receptor (NMDAR) antibodies in cerebrospinal fluid (CSF) and/or serum, there was no direct correlations between anti-NMDAR antibody titers in CSF and disease severity and prognosis in anti-NMDAR encephalitis patients. Here, we aimed to extensively identify CSF biomarkers related to the occurrence, development, and prognosis of anti-NMDAR encephalitis using a high-throughput proteomic approach. Methods A CSF cytokine antibody array containing 80 cytokines and inflammatory mediators related to immune and inflammatory responses was applied to identify biomarker candidates in individual CSF samples from a well-characterized cohort comprising patients with anti-NMDAR encephalitis (n = 6) and controls (n = 6). Validation and specific detection were performed in an extended cohort consisting of anti-NMDAR encephalitis patients (n = 13), controls (n = 13), and viral encephalitis (n = 13) by enzyme-linked immunosorbent assay (ELISA). Additionally, the levels of some inflammatory proteins in three groups in cohort 2 reported in previous literatures that may be involved in the development of anti-NMDAR encephalitis were also tested by ELISA. Correlations between candidate biomarkers and clinical characteristics of anti-NMDAR encephalitis patients were analyzed. Results Three differentially expressed cytokines and inflammatory mediators were screened from the 80-cytokine array in cohort 1. Functional enrichment analysis results suggested that these differentially expressed proteins were related to autophagy, immune/inflammatory responses, cell death, and other processes. In cohort 2, the elevations of cellular inhibitor of apoptosis protein-1 (cIAP-1), macrophage colony-stimulating factor (MCSF), CXC chemokine ligand 13 (CXCL13), and nucleotide binding oligomerization domain-like receptor protein 3 (NLRP3) in anti-NMDAR encephalitis were validated by ELISA. Linear regression revealed that the levels of CSF CXCL13 and cIAP-1 were positively correlated with the highest modified Rankin scale (mRS) score in the acute phase (p < 0.05). The level of cIAP-1 was positively correlated with the anti-NMDAR Encephalitis One-Year Functional Status (NEOS) score (p < 0.05). Conclusion These biomarkers show promising functions to evaluate severity or prognosis of anti-NMDAR encephalitis. The biological processes of immune/inflammatory responses, altered levels of autophagy, and the tumor necrosis factor (TNF) signal pathway may be involved in the pathophysiology of anti-NMDAR encephalitis to some extent.